Social services policy in the transition state the agenda of social reform in the Philippines - Reyes, Danilo R. (1987)
The problems of democratic regimes installed to power in societies that suffered and endured years of authoritarianism are generally varied and complex. In the early stages of reconstruction, the new government is confronted with a fragile and unwieldy environment. This is referred to as "the democratic conjuncture" or the transition state. In view of the unwieldy nature of the new configuration, the new regime has to reorder its priorities, which understandably requires a redefinition of the rules. As the new dispensation attempts with the aspirations of political and economic reconstruction. In the process, the active pursuit of social service programs designed to respond to the needs of the poor sectors of society may be deferred to allow the government to concentrate on the need to normalize and stabilize societal conditions. This pattern is analyzed using the Aquino government as frame of reference, as well as other countries presently engaged in redemocratization efforts. Some policy prescriptions towards improving delivery of social service programs once normalcy is attained are also proposed.
Keywords: Social service policies; Political transition